CORRELATION BETWEEN MALOCLUSION LEVELS AND ORAL HYGIENE STATUS IN SMAN 10 BANJARMASIN STUDENTS - Nur Annisa Islamiyati; Diana Wibowo; Riky Hamdani (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: A malocclusion is a form of deviation in the location of the teeth or malrelation of the jaw. Malocclusion can cause many problems, one of which is oral hygiene problems. Crowded teeth conditions cause difficulties in cleaning teeth, accumulated food debris can lead to plaque and calculus retention which is a predisposing factor for caries and gingivitis formation which affects the oral hygiene and health. Objective: To determine the relationship between the severity of malocclusion and oral hygiene status in students of SMAN 10 Banjarmasin. Method: This study was an observational study with a cross-sectional approach. The study population was students of SMAN 10 (Senior High School) Banjarmasin with age range of 15-18 years. The research sample was 97 respondents and the sampling technique used simple random sampling technique which was determined based on inclusion and exclusion criteria. Results: The highest malocclusion severity level of SMAN 10 Banjarmasin students was in the medium category with 34 people (43%). The oral hygiene status was the highest in the medium category with a total of 42 people (53.2%). The results of the data analysis found that there was a significant relationship of 0,000 (p < 0.05) between the severity of malocclusion and the oral hygiene status on the moderate category in students of SMAN 10 Banjarmasin. Conclusion: There is a relationship between the severity of malocclusion and oral hygiene status in SMAN 10 Banjarmasin students.